The Chinese Story of Yang Guifei in Japanese Novel the Tale of Genji and No Theater - Švambarytė, Dalia (Acta Orientalia Vilnensia, 2003)
Political, cultural and literary borrowings of Chinese origin are firmly rooted in the Japanese soil. Yang Guifei, a character of Chinese Tang dinasty, was made immortal by Bai Juyi, and through his poem The Song of Everlasting Sorrow made its way into Japanese literature. This article attempts to contribute to the discussion regarding the influence that her story made on Genji monogatari by concentrating on the polyphony of its reflections in personae and composition of Murasaki Shikibu’s narration, driving parallels between the temperaments in the Chinese poem, the Japanese novel and No drama Y6kihi and arguing their differences in the light of buddhist reintepretation of the Chinese morals in either The Tale of Genji or the No production. The article is supplied with Lithuanian translation of the Bai Juyi’s poem.